(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article explores advancements in the mechanisms used to neutralize harmful emissions in industrial settings. With the increasing emphasis on environmental sustainability and regulatory compliance, it is imperative to enhance emission control technologies. This study reviews existing literature on emission neutralization methods, proposes innovative techniques, and evaluates their effectiveness through experimental results. The findings underscore the importance of integrating advanced technologies into current practices to mitigate environmental impacts and promote public health.